The modulating effect of culture on the expression of dental anxiety in children: a literature review - M. O. FOLAYAN, E. E. IDEHEN, & O. O. OJO (Paediatric Dentistry, 2004)
The experience of anxiety is a universal human phenomenon. Studies have shown a world-wide variation in the prevalence of dental anxiety with estimates ranging between 3% and 43%.